The Study of Compound Sentences Found in It Ends with Us Novel by Colleen Hoover - I G B Wahyu Nugraha Putra; Putu Devi Maharani; I Kadek Agus Sugiantara (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2022)
This study focuses on analyzing the types of coordinating conjunction in compound sentences found in novel entitled “It Ends with Us” by Colleen Hoover. The aims of this study is to find out the types of coordinating conjunction in compound sentences. In this study, it used a descriptive qualitative method in describing the types of coordination in compound sentences based on the theory that proposed by Quirk and Greenbaum (1973). The total data found were 160 data (100%). In details, the percentage of the data syndetic coordination appears 134 data or 82%. The data consist of 71 data or 44% that used and as coordinator, 35 data or 21% that used but as coordinator, 15 data or 9% that used so as coordinator, and 13 data or 8% that used two coordinator of syndetic coordination. In addition, the percentage of the data asyndetic coordination appears 24 data or 16%. The data consist of 23 data or 15% that used coma (,) as coordinator, and 1 data or 1% that used semicolon (;) as coordinator. The rest is 2 data or 2% consist of both coordinator between syndetic and asyndetic coordination in compound sentence.